Structural design process for prefabricated roof truss system in Malaysia / Rezali Dewa - Dewa, Rezali (2015)
This study focuses on the structural design process for prefabricated roof truss system in Malaysia. To gain insights on the central focus of this study, three research objectives were addressed: 1) to identify the methods employed in the design of prefabricated roof truss system, 2) to determine the constraints in designing prefabricated roof truss system in accommodating the specifications, 3) to establish the structural design software capability in assisting the design decision-making of prefabricated roof truss system. Salient discoveries were obtained qualitatively, through in-depth interviews, and observations with the truss designers who are experts in the field of proprietary roof truss industry. Data analysis was conducted using NVivo version 10, simultaneously with data collection. Coding process validated the basis for emerging themes where meanings were comprehended and organized thematically. The findings painted a vivid picture of the truss designing experience. Firstly, the findings revealed the significant methods employed in the design of prefabricated roof truss system consist of two types of design: i) descriptive design method, ii) prescriptive design method. Initial conceptual design decision-making were highly characterized by technical experiences, user preference, attitudes towards requirements and specifications, constraints associated with design/construction stages, cost, raw materials, support-systems and production setup.Initial communication-related stress related to the players within and between players and acclimatizing to choices evolves towards offer and acceptance of the end product.Secondly, findings warranted the constraints in designing prefabricated roof truss system in accommodating the specifications were hindered by the limitations of the system itself, constructability, and conflict in the local standard practices. Thirdly, aspects of the structural design software capability assisting decision-making, relies on the perceived understanding by the users on what the software can/cannot do, level of expertise of the support system and setup in the trade scope of work in assisting the design decisionmaking of the prefabricated roof truss system.